2018
DOI: 10.1186/s13012-018-0718-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementation strategies to improve cervical cancer prevention in sub-Saharan Africa: a systematic review

Abstract: BackgroundDeveloped countries, such as the USA, have achieved significant decreases in cervical cancer burden since the introduction of Pap smear-based programs in the 1960s. Due to implementation barriers and limited resources, many countries in sub-Saharan Africa (SSA) have been unable to attain such reductions. The purpose of this review is to evaluate implementation strategies used to improve the uptake and sustainability of cervical cancer prevention programs in SSA.MethodsA reviewer (LJ) independently se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 85 publications
4
62
0
Order By: Relevance
“…Educational interventions were the most common type of intervention used to increase uptake of cervical screening in sub-Saharan Africa. The rationale for educational interventions is consistent with previous literature that names lack of knowledge or awareness as the most common barrier to cervical screening in low-and-middle-income countries and another review that found educational strategies were the most common among all cancer prevention efforts in sub-Saharan Africa [34,35]. Educational interventions were not very effective overall.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Educational interventions were the most common type of intervention used to increase uptake of cervical screening in sub-Saharan Africa. The rationale for educational interventions is consistent with previous literature that names lack of knowledge or awareness as the most common barrier to cervical screening in low-and-middle-income countries and another review that found educational strategies were the most common among all cancer prevention efforts in sub-Saharan Africa [34,35]. Educational interventions were not very effective overall.…”
Section: Discussionsupporting
confidence: 80%
“…Pap smears may also be more widely available in certain countries like South Africa. Another review of cervical cancer prevention in sub-Saharan Africa found that VIA was the most commonly used secondary screening method [35]. Both VIA and HPV testing have been declared strategies for closing the cancer divide between LMIC and high-income countries because of their costeffectiveness and feasibility [43] so the overrepresentation of Pap smear testing in our study may limit the generalizability and significance of our findings.…”
Section: Limitationsmentioning
confidence: 79%
“…Cervical cancer educational strategies have been shown to improve screening in studies which targeted rural populations of sub-Saharan Africa [12-14]. Erku et al describe that the odds of undergoing cervical cancer screening among women who had a comprehensive knowledge on cervical cancer and screening were 2.02 times higher than those who did not in a northwest Ethiopian population [8].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer remains a global health problem [4] especially in remote areas of developing countries [5,6]. Current cervical cancer screening is based on the pap smear cytology and has led to significant reduction in the incidence and death related to cervical cancer [6,7]. In depth understanding of the natural history of human papillomavirus (HPV) infection and related cervical neoplasia has led to the search of biomarkers which can improve the cervical cancer screening process.…”
Section: Introductionmentioning
confidence: 99%